Centrifugal Test and Instability Model Analysis of Excavation Surface Stability of a Shield Tunnel in a Clay Layer - Haoshuang Niu; Xiaolin Weng; Jibo Hu; Lele Hou (Frontiers in Earth Science, 2022)
In order to study the variation law of support pressure and instability mode of excavation face under different soil parameters, a complete set of centrifugal model seepage test device is independently developed. The results of centrifugal tests with different C/D (where C is the overburden thickness of the tunnel and D is the tunnel diameter), internal friction angles, and heights of water head show that with the increase of the retreating displacement S of the excavation surface, the support pressure P of the excavation surface can be divided into three stages: rapid decline (S < 1.5D%), slow rebound after reaching the limit support pressure Plim (1.5D% ≤ S ≤ 3D%), and gradually reaching the stable value (3D% < S). With the increase of C/D, the limit support pressure on the excavation face gradually increases and tends to be stable. For different soil properties, when C/D > 1.5, the limit support pressure on the excavation face tends to be stable. With the increase of internal friction angle, the limit support pressure decreases gradually, and its influence on support pressure can be ignored when φ > 40°. With the increase of height of water head Hw, the limit support pressure increases linearly. By establishing a numerical analysis model and analyzing the instability modes of soil under different C/D, internal friction angles, and cohesion, the instability mode of soil in front of the excavation face can have a great correlation with C/D of the soil and internal friction angle, while the influence of cohesion is minimal. With the increase of C/D, the soil changes from overall failure to local failure, the change of C/D mainly affects the height of soil arching effect and the width of the wedge below, while the internal friction angle mainly affects the width of the wedge and the instability angle of soil.